A Retrospective Study of Progression-Free and Overall Survival in Pediatric Medulloblastoma Based on Molecular Subgroup Classification: A Single-Institution Experience - Jiang, Tao; Zhang, Yuqi; Wang, Junmei; Du, Jiang; Raynald,; Qiu, Xiaoguang; Wang, Ying; Li, Chunde (Frontiers in Neurology, 2017)
Background: Medulloblastoma has been classified into four core subgroups according to the transcriptional profile in recent years. However, some disagreement among researchers remains regarding the prognoses and most effective treatments of the different subgroups with different age distributions. Objective: To analyze medulloblastoma prognosis in children population based on four molecular subgroups classification. Methods: From January 2011 to January 2013, 84 consecutive medulloblastoma patients aged underwent tumor removal at Beijing Tiantan Hospital. A total of 55 patients who ranged in age from 4-18 years underwent detailed follow-up. Molecular subgrouping was performed using RT-PCR. Results: The two-year progression free survival (PFS) and overall survival (OS) rates for the entire cohort were 76.2±5.8% and 81.8±5.2%, respectively. Univariate analysis revealed that the Group 4 patients had a better survival (two-year OS, 90.6±5.2%) than the SHH subgroup (P=0.002) and Group 3 patients (P=0.008). Only 2 of the 23 nonmetastasized Group 4 patients relapsed, and chemotherapy did significantly affect these patients (PFS, P=0.685). One out of five WNT patients had tumor relapse and died at last. LC/A histology and chemotherapy were independent risk factors in multivariate analysis. Conclusions: In our study, the nonmetastasized Group 4 patients had an excellent prognosis. The SHH subgroup and Group 3 patients had worst prognoses. LC/A histology had a dismal prognosis in our cohorts which warrants intensive treatment.